Racial/Ethnic Variations in Emergency Department Wait Times for Nontraumatic Dental Condition Visits in the United States - Okunseri, Christopher (2013)
BACKGROUND: Studies have documented an association between wait times in emergency departments (EDs) and quality of care for medical conditions, but little is known about trends and factors associated with wait times for nontraumatic dental condition (NTDC) visits in EDs. We examined trends in wait time and associated factors for NTDC visits in EDs in the United States. METHODS: We analyzed data from the National Hospital Ambulatory Medical Care survey for 1997 to 2007, with 2001-2002 excluded due to lack of wait time information. We used survey-weighted linear regression of log-transformed waiting time model for the wait time for NTDC visits. RESULTS: The geometric mean wait time for NTDC and non-NTDC visits was 29±1 and 25±0.6 minutes, respectively (p<0.0001). The geometric mean wait time for NTDC visits increased by 6% annually and from 20 minutes in 1997 to 37 minutes in 2007. Compared to Whites, Hispanics and Blacks had significantly longer wait times for NTDC visits (adjusted fold-difference [R] =1.2, 95% confidence interval [CI] = 1.13-1.31) and [R] = 1.3, [CI] = 1.29-1.38). Age, payer type, reason for visit and triaged category were significant predictors of wait time (R=2.3 and 2.4 for NTDC visits in triage category of 1-2 hours and >2-24hours respectively). CONCLUSION: Nationally, wait times in EDs for NTDC visits increased over time. Hispanics (aged ≤ 33years old) and Blacks waited longer to receive care for NTDCs in EDs than Whites. PRACTICE IMPLICATION: Prolonged wait times for NTDC visits in emergency departments could adversely impact quality of care and patient outcomes.